The function of the Roman army in southern Arabia Petraea - Castro, Mariana (Archaeopress Roman archaeology, 2019)
This volume provides a fresh perspective on the evolving and diverse functions of the Roman army in Arabia from the creation of the province to the end of the Byzantine period